2006
DOI: 10.1021/je0601210
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Liquid−Liquid Equilibria for Systems of (Sulfolane + Toluene or Chloronaphthalene + Octane)

Abstract: Tie-line data for ternary systems of (sulfolane + toluene + octane) at temperatures of 303.2 K and 313.2 K and (sulfolane + chloronaphthalene + octane) at temperatures of 298.2 K and 303.2 K are reported. The composition of liquid phases at equilibrium was determined by gas-liquid chromatography, and the results were correlated with the UNIQUAC and NRTL activity coefficient models to obtain the binary interaction parameters. Both the UNIQUAC and the NRTL models satisfactorily correlated the equilibrium composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…Considering the important role of a suitable solvent in the extraction process operations, the research for finding new solvents, in (liquid + liquid) extraction is an ongoing investigation [4][5][6][7][8]. In this line of research, the theoretical and experimental studies of (liquid + liquid) equilibrium (LLE) for different systems were presented in the literature [9][10][11]. The basic aim of these investigations was focused on the finding a non-toxic, inexpensive, and easily recoverable solvent for (liquid + liquid) extraction processes in the industrial units [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the important role of a suitable solvent in the extraction process operations, the research for finding new solvents, in (liquid + liquid) extraction is an ongoing investigation [4][5][6][7][8]. In this line of research, the theoretical and experimental studies of (liquid + liquid) equilibrium (LLE) for different systems were presented in the literature [9][10][11]. The basic aim of these investigations was focused on the finding a non-toxic, inexpensive, and easily recoverable solvent for (liquid + liquid) extraction processes in the industrial units [12].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we reported the LLE results for the mixtures (tetramethylene sulfone or dimethyl sulfoxide or ethylene carbonate + toluene or m-xylene + n-heptane or n-octane or cyclohexane) at different temperatures (298.5, 303.15, and 313.15) K [10][11][12]. On the basis of this work, it was suggested that ethylene carbonate as a solvent was more suitable than tetramethylene sulfone or dimethyl sulfoxide for extracting the aromatic hydrocarbon from alkane mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium apparatus used in the present work was similar to that used in the previous study [3]. The equilibrium cell is made of glass with a water jacket to maintain a constant 0021-9614/$ -see front matter Ó 2010 Elsevier Ltd. All rights reserved.…”
Section: Methodsmentioning
confidence: 99%
“…The separation of aromatic hydrocarbons from alkanes by solvent extraction processes has been an area of active research in various chemical, petrochemical, and oil industries [1][2][3]. Because of the known limitations of the direct separation processes such as distillation for practical extraction of the constituent components of the non-ideal mixtures, the indirect separation processes such as solvent extraction may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid–liquid extraction (LLE) of chloropropanols appears as another convenient choice for DCP upgrading. In order to understand and design a proper solvent extraction process, reliable liquid–liquid phase equilibria data are necessary. , …”
Section: Introductionmentioning
confidence: 99%